AFL learners' perception of virtual treasure hunt in learning vocabulary - Mohamad Helni, Mohamad Ikmal Hakimi (2022)
Vocabulary has been considered as one of the most fundamental bases in language learning. The learning of vocabulary is very crucial to foreign language learners as it is directly related to all language skills. Since learning vocabulary is of a paramount importance to foreign language learners, different approaches have been implemented which among them is by using Virtual Treasure Hunt (VTH) as a module. Therefore, this research aims to investigate AFL learners’ perception of Virtual Treasure Hunt (VTH) in learning vocabulary. This research employs a qualitative approach which specifically uses descriptive qualitative design. The participants of this research were among the AFL learners of the Centre for Foundation Studies (CFS) International Islamic University Malaysia (IIUM) who are enrolled for elementary levels of Quranic language. The data collection technique is an interview. This research discovered that learners found Virtual Treasure Hunt (VTH) is effective to attract them in learning vocabulary in a more fun, easy way. Furthermore, the learners also stated the advantages of Virtual Treasure Hunt (VTH) which it involves in helping them acquiring new vocabulary in a more imaginary way. In addition, this research also found that Virtual Treasure Hunt (VTH) contributes to a more engaging learning environment though it is held virtually. The findings imply that Virtual Treasure Hunt (VTH) is beneficial for AFL learners to master vocabulary and the teachers should utilise this approach well.